An Endoscope Manipulating Robot Design. Issue 2 (June 2019) - Xiaohui, Xie; Xiuan, Zhang; Lining, Sun; Gongxian, Wang; Yue, Yu; Cheng, Zhang; Xiaochen, Zhou
Abstract: This paper mainly studies a new type of endoscope manipulating robot to replace the nurse or assistant to manipulate and hold the endoscope in surgery. By analyzing the operating environment of minimally invasive surgery, the paper presented the basic requirements of the endoscope manipulating mechanism design, and developed a endoscope manipulating system with seven degree of freedom. In order to meet the intraoperative spatially invariant point required by the minimally invasive surgery, a new romote-center-of- motion(RCM) mechanism, parallelogram RCM mechanism, was designed by improving composite parallelogram mechanism. In addition, a wire-driven modular joint with single-degree-of- freedom was also developed, which has been used for the endoscope operating in-out the human body. The motion test of RCM mechanism shows that the robot has good flexibility and can fully meet the design requirements of the endoscope manipulating mechanism.